MECT1-MAML2 Fusion Transcript Defines a Favorable Subset of Mucoepidermoid Carcinoma - Okabe, Mitsukuni; Miyabe, Satoru; Nagatsuka, Hitoshi; Terada, Akihiro; Hanai, Nobuhiro; Yokoi, Motoo; Shimozato, Kazuo; Eimoto, Tadaaki; Nakamura, Shigeo; Nagai, Noriyuki; Hasegawa, Yasuhisa; Inagaki, Hiroshi (Clinical cancer research, 2006)
Purpose: Mucoepidermoid carcinoma is the most common primary malignancy of the salivary gland. Mucoepidermoid carcinoma translocated gene 1-mastermind-like gene family ( MECT1-MAML2 ) gene fusion was identified from a recurring t(11;19)(q21;p13) translocation, which is often the sole cytogenetic alteration in this disease. This fusion transcript has been frequently detected in mucoepidermoid carcinoma and shown to be involved in the transformation of epithelial cells. However, its clinicopathologic significance remains unclear. Experimental Design: Seventy-one cases of mucoepidermoid carcinoma and 51 cases of nonmucoepidermoid carcinoma salivary gland tumors (including 26 Warthin tumor cases) were retrospectively analyzed. RNA was extracted from archival materials: histologic paraffin specimens in all cases and cytologic specimens in 10 mucoepidermoid carcinoma cases. The MECT1-MAML2 fusion transcript was detected by a reverse transcription-PCR assay, which can be applied to both histologic and cytologic specimens. The presence of the fusion transcript was correlated with relevant clinicopathologic and survival data of the mucoepidermoid carcinoma patients. Results: The MECT1-MAML2 fusion transcript was detected in 27 of the 71 (38%) mucoepidermoid carcinoma cases but not in any case of nonmucoepidermoid carcinoma tumors. The reverse transcription-PCR results showed no difference between histologic and cytologic specimens. Detection of the MECT1-MAML2 fusion transcript was associated with a less advanced clinical stage and a low-grade tumor histology. The presence of the transcript was associated with longer disease-free and overall survivals on univariate analysis and emerged as an independent prognostic factor for longer overall survival on multivariate analysis. Conclusions: The MECT1-MAML2 fusion transcript may be specific to mucoepidermoid carcinoma and associated with a distinct mucoepidermoid carcinoma subset that exhibits favorable clinicopathologic features and an indolent clinical course.